Machine learning espousal in signal processing : applications, challenges and road ahead - Tanwar, Sudeep; Nayyar, Anand; Rameshwar, Rudra (Boca Raton : Chapman & Hall/CRC Press, 2022)
"Machine Learning in Signal Processing: Applications, Challenges and Road Ahead offers a comprehensive approach towards research orientation for familiarising 'signal processing (SP)' concepts to machine learning (ML). Machine Learning (ML), as the driving force of the wave of Artificial Intelligence (AI), provides powerful solutions to many real-world technical and scientific challenges. This book will present the most recent and exciting advances in signal processing for Machine Learning (ML). The focus is on understanding the contributions of signal processing and ML and its aim to solve some of the Artificial Intelligence (AI) and Machine Learning (ML) challenges"--
OCLC-licensed vendor bibliographic record.
Keywords: Machine learning; Signal processing; COMPUTERS / Machine Theory